BIOGRAFI ABDUL RAHMAN: DARI DOSEN HINGGA POLITISI KABUPATEN SOLOK SELATAN TAHUN 2000-2010 - Ekasari, Gusnarti; Husnita, Liza; Aziz, Zul Kifli (Pendidikan Sejarah, 2014)
Abdul Rahman is a politician in South Solok, but before becoming a politician Abdul Rahman is a lecturer of the University Law Jayabaya Jakarta. This study aims to describe the biography of Abdul Rahman Lecturer Until Politicians From South Solok Year 2000-2010. The method used in this study is the method of historical research descriptive analytical study sites in South Solok. As for the stages following the method used, the first heuristic is the activity of collecting sources such as documents, records and interviews. The second criticism is the source of events to test the sources that have been collected through internal and external criticism. The third interpretation is an activity to interpret the facts with the fact that one way of connecting with other facts in accordance with the historical events that includes the time, place and event. Â Historiography is the fourth presents the results of researchin the form of a thesis.These results indicate that : Abdul Rahman is a figure of the faculty as a lecturer and herein Abdul Rahman started his career by devoting himself as a teacher for four years from 2000-2004, but in 2004 there is expansion and South Solok Regency is one of which is initially Solok and a halamanya his own hometown. Given this expansion Abdul Rahman tried to join in the party and the PAN Party Politi exactly a lot of support from the community. In the election of 2005 Abdul Rahman was elected as chairman in 2005-2010 and DPD PAN second period Abdul Rahman reelected the 2010-2014 period, in the 2009 elections Abdul Rahman was elected as Vice Chairman of the Parliament of South Solok in addition, in the elections of 2010 Abdul Rahman was elected as Vice Regent in South Solok. While serving as Vice Regent Abdul Rahman has started to fix the South Solok, in terms of the development has been a lot of visible changes as well as in education. Despite little change but Abdul Rahman has begun to show improvement in these areas and this has already occurred well and got a goodreception from the public.